Scintigraphic Detection of Gynaecological Tumours by 99mTc-HSA Blood Pool Imaging - Georgiou, E. C.; Arkas, A. Z.; Alevizaki, C. C.; Gnafakis, N. (Nuklearmedizin - NuclearMedicine, 1979)
Three cases of scintigraphic visualization of gynaecological tumours by 99mTc-HSA blood pool imaging are presented, i.e. one case of fibrothecoma (“cold” area visualization) and two cases of fibromyoma (“hot” area visualization). It is suggested that this technique may be useful in the preoperative evaluation of gynaecological tumours and their vascularity.